Optimalisasi Peran Perawat sebagai Upaya Meningkatkan Kualitas Pelayanan Keperawatan di Ruang Penyakit Dalam Rumah Sakit Regional Eduardo Ximenes (HoREX) Baucau, Timor-Leste: Optimizing the Role of Nurses as an Effort to Improve the Quality of Nursing Services in the Internal Medicine Room of the Eduardo Ximenes Regional Hospital (HoREX) Baucau, Timor-Leste - Belo, Saturnina Fernandes; Suhita, Byba Melda (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Nursing services are an integral part of healthcare delivery and play a critical role in improving hospital service quality. Nurses, as the healthcare professionals who interact most frequently with patients, have a strategic role in determining the quality of nursing services, particularly in internal medicine inpatient wards. This study aimed to analyze the relationship between the role of nurses and the quality of nursing services in the Internal Medicine Ward of Eduardo Ximenes Regional Hospital (HoREX) Baucau, Timor-Leste. This study employed a quantitative correlational design with a cross-sectional approach. The sample consisted of nurses working in the Internal Medicine Ward of HoREX Baucau, selected using a total sampling technique. Data were collected using a questionnaire assessing nurses’ roles in nursing services and analyzed using statistical tests with SPSS software. The findings showed that the role of nurses in nursing services was categorized as good. Statistical analysis indicated a significant relationship between nurses’ roles and the quality of nursing services, as evidenced by statistically significant test results. Nurses’ roles have a significant contribution to improving the quality of nursing services. Strengthening and optimizing nurses’ roles through managerial support and continuous evaluation are essential to achieve high-quality nursing services and improved patient satisfaction.